Rabindranath Tagore and fifty years of Sahitya Akademi - Biswajit Sinha (Eastern Book Linkers, 2006)
Articles on the influence of Rabindranath Tagore, 1861-1941, Bengali author, on the publishing activities, seminars, and awards initiated by Sahitya Akademi, the Academy of Letters of India, for the last fifty years.